(untitled) (SCIÉNDO INGENIUM, 2021)
The objective of this research was to analyze the work of the university professor as a teacher and researcher and for this a systematic review study of the literature was carried out. The study was developed following the guidelines of the Scientific Research Methodology established by the Graduate School and used for this purpose the inductive, deductive and hermeneutical methods with the support of the document analysis sheet instrument. It is concluded that research offers teaching the opportunity to discover new topics of interest and becomes the support for teaching. In this way, teaching work based on investigative practice allows the disciplinary and professional training of students. Hence the importance that the teacher not only master’s scientific knowledge as an object of teaching or relies on cognitive theories of learning that allow explaining the process of construction of knowledge, but also can design a learning situation articulating problems of the context with disciplinary knowledge and, in this way, the future professional will be able to function ideally in a multicultural and globalized society.